2014
DOI: 10.1002/ana.24128
|View full text |Cite
|
Sign up to set email alerts
|

KCNT1 gain of function in 2 epilepsy phenotypes is reversed by quinidine

Abstract: Objective Mutations in KCNT1 have been implicated in autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) and epilepsy of infancy with migrating focal seizures (EIMFS). More recently, a whole exome sequencing study of epileptic encephalopathies identified an additional de novo mutation in one proband with EIMFS. We aim to investigate the electrophysiological and pharmacological characteristics of hKCNT1 mutations and examine developmental expression levels. Methods Here we use a Xenopus laevis oocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
258
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 277 publications
(275 citation statements)
references
References 29 publications
16
258
0
1
Order By: Relevance
“…Mutations in the gene for K Na 1.1 have also been documented in autism (Iossifov et al, 2014). When expressed in Xenopus oocytes, the disease-causing mutations in K Na 1.1 generate currents that are 3-to 22-fold greater than those of wild-type channels, with no change in levels of channel protein or mRNA (Barcia et al, 2012;Martin et al, 2014;Milligan et al, 2014). For a subset of these mutations, changes in voltage dependence or Na + sensitivity contribute to the increase in current Tang et al, 2016).…”
Section: The K Ca 2 Family-small Conductance Channels Regulated mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the gene for K Na 1.1 have also been documented in autism (Iossifov et al, 2014). When expressed in Xenopus oocytes, the disease-causing mutations in K Na 1.1 generate currents that are 3-to 22-fold greater than those of wild-type channels, with no change in levels of channel protein or mRNA (Barcia et al, 2012;Martin et al, 2014;Milligan et al, 2014). For a subset of these mutations, changes in voltage dependence or Na + sensitivity contribute to the increase in current Tang et al, 2016).…”
Section: The K Ca 2 Family-small Conductance Channels Regulated mentioning
confidence: 99%
“…Quinidine is a very effective blocker of these channels in both expression systems and neurons (Bhattacharjee et al, 2003;Yang et al, 2006Yang et al, , 2007Milligan et al, 2014;Rizzo et al, 2016). It has been reported that quinidine ameliorated the symptoms of a patient with malignant migrating partial seizures in infancy, but because this agent blocks a wide variety of other channels, the mechanism is not known (Bearden et al, 2014).…”
Section: The K Ca 2 Family-small Conductance Channels Regulated mentioning
confidence: 99%
“…Functional assays that will be reported elsewhere have confirmed that this mutation activates KCNT1 channels similarly to previously reported NFLE-associated mutations. 23 The other 2 variants (in T2957 and T2958; table 3) are of uncertain significance at this time based on the TLE phenotype and unavailability of parental samples for segregation.…”
mentioning
confidence: 95%
“…These mutations are associated with a gain of function of the mutant ion channel 16. This gain of function can be reversed in vitro by an “old” drug, quinidine, which targets the KCNT1 potassium channel 17. Quinidine is both an antiarrhythmic agent and antimalarial treatment.…”
Section: Proposal For a Framework For Epilepsy Classification And Diamentioning
confidence: 99%